Peptidomic analysis of endogenous plasma peptides from patients with pancreatic neuroendocrine tumours - Richard G. Kay; Benjamin Challis; Ruth Casey; Geoffrey Roberts; Claire L. Meek; Frank Reimann; Fiona M. Gribble (2018)
Diagnosis of pancreatic neuroendocrine tumours requires the study of patient plasma with multiple immunoassays, using multiple aliquots of plasma. The application of mass spectrometry based techniques could reduce the cost and amount of plasma required for diagnosis.Plasma samples from two patients with pancreatic neuroendocrine tumours were extracted using an established acetonitrile-based plasma peptide enrichment strategy. The circulating peptidome was characterised using nano and high flow rate liquid chromatography/mass spectrometry (LC/MS) analyses. To assess the diagnostic potential of the analytical approach, a large sample batch (68 plasmas) from control subjects, and aliquots from subjects harbouring two different types of pancreatic neuroendocrine tumour (insulinoma and glucagonoma), were analysed using a 10-min LC/MS peptide screen.The untargeted plasma peptidomics approach identified peptides derived from the glucagon prohormone, chromogranin A, chromogranin B and other peptide hormones and proteins related to control of peptide secretion. The glucagon prohormone derived peptides that were detected were compared against putative peptides that were identified using multiple antibody pairs against glucagon peptides. Comparison of the plasma samples for relative levels of selected peptides showed clear separation between the glucagonoma and the insulinoma and control samples.The combination of the organic solvent extraction methodology with high flow rate analysis could potentially be used to aid diagnosis and monitor treatment of patients with functioning pancreatic neuroendocrine tumours. However, significant validation will be required before this approach can be clinically applied.